2022
DOI: 10.1017/rdc.2022.89
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Mortar Charcoals From Medieval Rýzmburk Castle, Northwestern Bohemia

Abstract: Rýzmburk Castle is one of the largest and most important medieval castles in Bohemia, documented since 1250 AD. Its North tower is assumed to be built in 1260–1300 AD. To test this assumption, the surface layers of mortar were inspected for the presence of charcoals suitable for radiocarbon dating, and 10 charcoals were found. The charcoals probably originated from wood used for lime burning. The results of radiocarbon dating using accelerator mass spectrometry agree with the historical estimation. Single post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For comparison, analogous results are presented for the northern tower of Rýzmburk (Figure 3C), the bergfried of Týřov (Figure 3D), the tower and buttress of Pyšolec (Figure 3E), and the Southern Corridor of Bishopric District of Prague Castle (Figure 3F), based on previously presented samples (Kundrát et al 2022;Pachnerová Brabcová et al 2022a, 2022b, 2022c; samples of Paleolithic origin or identified as old wood or young intrusions were excluded. As the KDE method in Oxcal is based on stochastic Markov chain Monte Carlo simulations, its results slightly differ from run to run, and the present results are not identical with those reported previously, yet the basic characteristics remain unchanged.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For comparison, analogous results are presented for the northern tower of Rýzmburk (Figure 3C), the bergfried of Týřov (Figure 3D), the tower and buttress of Pyšolec (Figure 3E), and the Southern Corridor of Bishopric District of Prague Castle (Figure 3F), based on previously presented samples (Kundrát et al 2022;Pachnerová Brabcová et al 2022a, 2022b, 2022c; samples of Paleolithic origin or identified as old wood or young intrusions were excluded. As the KDE method in Oxcal is based on stochastic Markov chain Monte Carlo simulations, its results slightly differ from run to run, and the present results are not identical with those reported previously, yet the basic characteristics remain unchanged.…”
Section: Resultsmentioning
confidence: 87%
“…The third site is the northern tower of Rýzmburk castle (Pachnerová Brabcová et al 2022a), previously dated to the early phase of Rýzmburk development, 1260-1278 or pre-1300 (Lehký 2012; Razím 2019). Fourth, inclusions were analyzed from the bergfried of Týřov castle (Pachnerová Brabcová et al 2022b); the previous results were extended by three wood samples.…”
Section: Introductionmentioning
confidence: 99%
“…absolute dating of the lime mortars is mainly used. In radiocarbon dating of mortars, the charcoal embedded in the mortar (e.g., [19][20][21][22][23][24][25][26][27]) or the lime binder (e.g., [28][29][30][31][32][33][34]) are used. Nevertheless, the use of charcoal fragments should be used with caution due to the effects of old wood [35].…”
Section: Introductionmentioning
confidence: 99%